Re-actualisation of puppet characters in modern Indonesian fictions of the 21st century - Nurgiyantoro, Burhan; Efendi, Anwar (Penerbit Universiti Kebangsaan Malaysia, 2017)
Indonesian fiction works of the 21st century often intertextualise with puppet stories and characters. Puppet stories and characters, used as sources and references, inspire the creation of modern Indonesian fiction. Puppet stories are canonic works originating from mainstream Mahabharata and Ramayana, thematically narrating the heroism of good characters in defeating evil characters. Reactualisation of puppet stories and characters in literature is a redefinition and contextualisation as a response to the chalenges of time. Analyses of the intertextuality between Indonesian fiction and puppet stories and characters show the following things. First, Indonesian fiction is seen as intensively intertextualising with puppet stories and characters. Many puppet characters that are actualised originate more from the mainstream Mahabharata than from the mainstream Ramayana. Characters with good traits are made protagonists and characters with evil traits are made antagonists. Second, Indonesian fiction uses the identities of puppet characters as name references. References of puppet character identities take the form of hypograms of names with characters, names without characters, and characters without names. The most intensive identity referencing of puppet characters in the form of hypogramming to continue convention is naming with characters. Third, Indonesian fiction uses puppet stories and characters as cultural references. Puppet hypograming is taken to function as cultural references, comparison purposes, means of children education, and reincarnation sources in the Hindu religion. Cultural referencing of puppets is more efficient and communicative as it is typological, following the mainstreams and exact.